A Notion of Equilibrium in Relational Form Games and Politics - Pâquet, Sylvain (Université d'Ottawa / University of Ottawa, 2018)
This dissertation consists of a development of the notion of equilibrium in non-cooperative games (introduced by John Nash in his doctoral dissertation submitted in May 1950) from the point of view of games played by complex adaptive systems (such as States) who adapt to an asymmetric distribution of bargaining power. The main ingredient of this dissertation is the notion of the contextually normalized solution, that implies that players routinely repeat strategies that work, and that an asymmetric complex game will be in a stable state so long as the set of normal strategies consists of the stronger players’ most preferred and the weaker players’ least disliked strategies. There is no other generality in rational behaviour; all else is relative to the frame of reference.
Keywords: complex adaptive system; contextually normalized solution; equilibrium; game theory; international relations; normalization; relational form game; State behaviour